Asupan vitamin B3 (niasin), C, E, dan serat berhubungan dengan dislipidemia pada penyakit jantung koroner di RS DR. Mohammad Hoesin Palembang - Muzakar Muzakar; Kris Dinarti; Herni Astuti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2010)
Background: Coronary heart disease is a health problem both in developed and developing countries including Indonesia. The result of household health survey in 1992 and 1995 indicated that coronary heart disease was the first cause of death with the prevalence as much as 16.5% and 19% subsequently. Coronary heart disease is caused by many factors such as hypertension, hyperlipidemia, obesity, smoking and diabetes mellitus. High intake of unsaturated fat for a long time can increase blood lipid level. Efforts to lowering blood cholesterol can be made by managing macro nutrient intake as well as micro nutrient intake such as vitamin B3, C, E, and fibers.Objective: To find out the relationship between intake of vitamin B3 (niacin), C, E and fibers and dyslipidemia in coronary heart disease at dr. Mohammad Hoesin Hospital of Palembang.Method: The study was analytic observational which used cross sectional design. Subject of the study were dyslipidemia patients of coronary heart disease who were newly diagnosed. There were as many as 50 patients who fulfilled inclusion and exclusion criteria and were purposively chosen. The study was carried out at cardiology room from October 2007 to February 2008. Data of intake were obtained from questionnaires of quantitative food frequency and processed using computer. Chi square test was used to identify the relationship between intake and lipid profile; Spearman rho correlation was used to find out the level of relationship; and odds ratio was used to identify the risk.Result: There was significant relationship between intake of vitamin B3, C, E and fibers and total cholesterol (p < α). There was significant relationship between intake of vitamin E and triglyceride (p = 0.015). There was significant relationship between intake of vitamin B3, E and fibers and high density lipoprotein cholesterol (p < α). There was significant relationship between intake of vitamin B3, C, E and fibers and low density lipoprotein cholesterol (p < α).Conclusion: There was relationship between low intake of vitamin B3, C, E and fibers of dyslipidemia patients in coronary heart disease.